Risk profiling based on p16 and HPV DNA more accurately predicts location of disease relapse in patients with oropharyngeal squamous cell carcinoma. (18th January 2019) - Rasmussen, J H; Grønhøj, C; Håkansson, K; Friborg, J; Andersen, E; Lelkaitis, G; Klussmann, J P; Wittekindt, C; Wagner, S; Vogelius, I R; von Buchwald, C
Abstract: Background: In the era of precision medicine and HPV-related oropharyngeal squamous cell carcinoma (OPSCC), it is relevant to assess the risk of not only survival, but also the risk of local, regional, or distant treatment failure. The UICC 8th edition uses the surrogate marker p16 to stratify for HPV association but discordance between p16 status and HPV association has been shown. The purpose of this study was to develop a prognostic model to predict the risk of local, regional, and distant metastases and non-cancer-related death for patients with OPSCC, test the prognostic relevance of adding HPV DNA and p16 status, and validate the findings in an independent external dataset. Patients and methods: Consecutive patients diagnosed with OPSCC and treated with curative radiotherapy with or without cisplatin in eastern Denmark from 2000 to 2014 were included. Characteristics included age, gender, TNM stage, smoking habits, performance status, and HPV status assessed with p16 and HPV DNA. The information was used to develop a prognostic model for first site of failure with four competing events: recurrence in T-, N-, and M-site, and death with no evidence of disease. Results: Overall 1243 patients were eligible for the analysis. A prognostic model with the four events was developed and externally validated in an independent dataset with a heterogeneously treated patient population from another institution. The individual prognostication from the competing risk analysis is displayed in a user friendly online tool (https://rasmussen.shinyapps.io/OPSCCmodelHPV_p16/ ). Replacing p16 status with the combined variable HPV/p16 status influenced the HR and patients with HPV−/p16+ had significantly higher HR of M-site recurrence than HPV+/p16+ with a HR = 2.56; CI [1.30; 5.02]; P  = 0.006 ( P  = 0.013 in the validation cohort). Conclusion: Patients with HPV−/p16+ have significantly higher risk of M-site recurrence and could potentially be relevant candidates for clinical trials testing systemic treatments in combination with conventional treatments.